2009
DOI: 10.1016/j.cognition.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Categorical structure among shared features in networks of early-learned nouns

Abstract: The shared-features that characterize the noun categories that young children learn first are a formative basis of the human category system. To investigate the potential categorical information contained in the features of early-learned nouns, we examine the graph-theoretic properties of noun-feature networks. The networks are built from the overlap of words normatively acquired by children prior to 2 ½ years of age and perceptual and conceptual (functional) features acquired from adult feature generation nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 53 publications
7
113
0
Order By: Relevance
“…Recall that early in development, semantic representations are poorly differentiated but become increasingly differentiated in accordance with taxonomic relations in the course of learning and development Hills, et al, 2009;Kemp & Tenenbaum 2008;Rogers & McClelland, 2004;Unger et al, 2014). For example, Unger et al (2014) observed that preschoolers and kindergarteners were likely to group together items, such as whale, seaweed, and water lily (likely due to similarity in habitat); however, by second grade children grouped items largely in accordance with the plants-animals distinction.…”
Section: Novel Predictions Of the Pars Accountmentioning
confidence: 99%
See 3 more Smart Citations
“…Recall that early in development, semantic representations are poorly differentiated but become increasingly differentiated in accordance with taxonomic relations in the course of learning and development Hills, et al, 2009;Kemp & Tenenbaum 2008;Rogers & McClelland, 2004;Unger et al, 2014). For example, Unger et al (2014) observed that preschoolers and kindergarteners were likely to group together items, such as whale, seaweed, and water lily (likely due to similarity in habitat); however, by second grade children grouped items largely in accordance with the plants-animals distinction.…”
Section: Novel Predictions Of the Pars Accountmentioning
confidence: 99%
“…In contrast, when reasoning about novel artificial categories, children's inferences cannot be category-consistent in their outcome without being categorybased in their mechanism. Newly learned artificial categories are based on a small number of shared features and their representations are likely not sufficiently differentiated to support inferences based on representational similarity (Hills, et al, 2009;Kemp & Tenenbaum 2008;Rogers & McClelland, 2004). Therefore, inconsistencies in the developmental trajectory of inductive generalization that have emerged across different studies can be explained by the notion of representational similarity.…”
Section: Inconsistencies In Developmental Trajectoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the advantages of network analysis is that it allows researchers to study phenomena at scales that range from individual words (i.e., nodes) to the entire lexicon (i.e., the network). Network analyses have been widely used to study the large scale structures of associative networks (De Deyne, Navarro, & Storms, 2013;De Deyne & Storms, 2008a;Steyvers & Tenenbaum, 2005), the formation of categories in toddlers (Hills, Maouene, Maouene, Sheya, & Smith, 2009a), and the trajectories of network development during early life (Bilson, Yoshida, Tran, Woods, & Hills, 2015;Hills et al, 2009b).…”
Section: Associative Change Across the Lifespanmentioning
confidence: 99%